Development of Bioactive Edible Film and Coating Obtained from Spirogyra sp. Extract Applied for Enhancing Shelf Life of Fresh Products - Siriwan Soiklom; Wipada Siri-anusornsak; Krittaya Petchpoung; Sumpan Soiklom; Thanapoom Maneeboon (Foods)
The growing interest in environmentally friendly food packaging has led to the development of bio-edible alternatives. This study developed novel, edible, active films and coatings to enhance the shelf life of fresh products. Crude bioactive algal extract (CBAE) was obtained from the ethanol extraction of Spirogyra sp. and incorporated into chitosan-based films and coatings at varying concentrations. The CBAE was rich in phenolic compounds and had antioxidant activity and potential antibacterial properties. The films were prepared using a solvent-casting method and characterized for their biochemical and physical properties. The incorporation of CBAE enhanced the antioxidant activity and improved the tensile strength of the films by 80%. Additionally, film transparency and water vapor permeability were reduced by 13% and 50%, respectively, compared to the control. The developed CBAE coating solution exhibited biocompatibility with human colon adenocarcinoma (HT-29) and mouse subcutaneous connective tissue (L929) fibroblast cells. A shelf-life evaluation using a coating-dipping method on okra showed that the CBAE-coated samples maintained better weight retention and firmness than the uncoated samples over 5 days of storage at ambient temperature. Based on these findings, the CBAE-based edible films and coatings could serve as sustainable alternatives for extending the shelf life of fresh products.